PENGARUH KREDIT, INOVASI, DAN MANAJEMEN USAHA TERHADAP KINERJA KEUANGAN KOPERASI SIMPAN PINJAM - Nuning Nurna Dewi (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
This study aims to examine and analyze the effect of credit, innovation, and business management on the financial performance of savings and loan cooperatives in 8 districts in East Java. Technique of data retrieval is done by interview and kuisoner. In addition to interviews, researchers also used the financial statements of savings and credit cooperatives in 2005-2008 to determine the value of ROI (Return On Investment) on each saving and loan cooperatives. Data analysis technique in this research is done by technical analysis of inferential data. The results showed that the amount of credit, cost of innovation, and business management have a significant effect on ROI.